Hukum Perjanjian Syariah: Asas-asas hukum perjanjian syariah - Maulina, Anisa Turrohmatul (Maliki Interdisciplinary Journal, 2024)
In terms of "akad" (agreement) has an important meaning in society. The akad is "the basis of some of our daily practices to know how to give the akad properly." For example through the akad a man joins a woman in a special life, and through the akad also various business practices. akad works with each individual in addressing his needs and interests which he cannot satisfy without the help and administration of others. He is in this way legitimate to say that contract is a social method invented by human development to help his life as a social being. In Islamic regulations there are hidden standards of understanding their implementation and execution. In this article there are nine standards of understanding (Akad) which can be used as a reason to suspect and reasonably execute an arrangement that is Islamically lawful. When a person enters into a contract, he automatically fulfills the principles of the sharia agreement because as a functional regulator of society, the contract is based on sharia.